Factors Related to Physical Activity Behavior Among Breast Cancer Patients in Dr. Sardjito General Hospital Yogyakarta - Cicirosnita Jayadi Idu; Haryani Haryani; Uki Noviana (http://dharmais.co.id/, 2023)
Background: Breast cancer patients are likely to have reduced physical activity behavior after being diagnosed. Factors associated such as sociodemographic and clinical health status have been investigated in some countries, but few studies have been conducted in Indonesia. Therefore, this study aimed to determine the sociodemographic factors and clinical health status associated with changes in physical activity behavior among breast cancer patients.Methods: A cross-sectional design was used and the samples included a total of 250 breast cancer patients at the Integrated Nuclear Medicine and Cancer Installation, Dr. Sardjito Hospital Yogyakarta. The samples were selected using the consecutive sampling method from June to July 2021, while the instruments employed had been previously tested for their validity and reliability. These included a questionnaire on the characteristics of sociodemographic and clinical health status, the Visual Analogue Scale (VAS), the Brief Fatigue Inventory (BFI), and the International Physical Activity Questionnaire Form (IPAQ-SF). This study obtained ethical clearance, while data were analyzed using chi-square and logistic regression multinominal tests with p<0.05.Results: The results showed that cancer stage (stage III: OR=2.71, 95%CI:1.14-6.45), fatigue (severe fatigue: OR=0.49, 95% CI:0.25-0.96), and pain (mild pain: OR= 27.44, 95%CI:3.20-235.18), were significantly associated with physical activity behavior in breast cancer patients. Pain as the most dominant factor (mild pain: OR=20.388, p=0.001) caused 5 times increased risk of reduced physical activity compared to others. Conclusions: Based on the results, cancer stage, fatigue, and pain were significantly related to the physical activity behavior of breast cancer patients, with pain being the most dominant factor.